DEEP LEARNING IN IMPROVING STUDENTS' MATHEMATICAL CRITICAL THINKING: A SYSTEMATIC LITERATURE REVIEW: Bali, Indonesia - I Kadek Agus Prabawan Saputra; I Putu Pasek Suryawan; I Gusti Ngurah Pujawan (Universitas Muhammadiyah Bengkulu, 2026)
Mathematical critical thinking skills are one of the essential competencies that students must have in 21st-century mathematics learning. However, learning practices in schools still tend to be oriented towards procedural mastery and formula memorization, so they are not optimal in developing students' higher-order thinking skills. One approach that is considered relevant to overcome this problem is deep learning, which emphasizes meaningful understanding, interrelationships between concepts, reflection, and the application of knowledge in real contexts. This study aims to analyze the implementation of deep learning in improving students' mathematical critical thinking skills. The research method used is a systematic literature review with a descriptive qualitative approach to relevant national articles. This study reviews 20 research articles obtained from the Google Scholar database with a publication range from 2025 to 2026. The results of the study show that deep learning is able to encourage students to analyze mathematical problems in depth, evaluate solution strategies, and construct logical mathematical arguments. Thus, deep learning has the potential to be an effective approach in improving the quality of mathematics learning. Keywords: Deep Learning, Mathematics Learning, Mathematical Critical Thinking